Pokolenia X, Y i Z wobec reklamy internetowej - Sadowa, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In the last 20 years the two decades of the 21st century, there have been visible changes in the behavior of buyers under the influence of the Internet. Virtual communication has become widespread, which has significantly changed the structure of advertising expenditures — the share of online advertising in the advertising pie is constantly increasing. Online advertising undoubtedly affects the representatives of generations X, Y and Z, which are distinguished in the literature due to different character traits, views, behaviors, as well as the attitude to new technologies. The aim of the considerations is to recognize the impact of online advertising on the purchasing behavior of representatives of generations X, Y and Z in Poland. Two research hypotheses were formulated. First of all, online advertising affects the purchases of all the generations analysed. Secondly, the generations Y and Z most commonly tend to be inclined to purchase by advertisements posted on social networks. To achieve the goal a section of the author’s original quantitative research was used, which was carried out at the turn of 2017 and 2018 on a sample of 660 respondents in Poland 487 and Great Britain 173.
Keywords: generation X; generation Y; generation Z; advertising; internet advertising; consumer behavior